Chinese International Scholars’ Work–Life Balance in the United States: Stress and Strategies - Su-Russell, Chang; James, Anthony (Journal of International Students, 2021)
Acculturative stress and strategies have been investigated with undergraduate international students in the United States. However, not much is known about scholars who come to the United States for advanced educational or career opportunities. Guided by Berry’s (2006) acculturative stress coping adaptation theory, the current study explored lived experiences of CISs through longitudinal interviews. Inductive analysis revealed themes about stressors that challenged work–life balance. Three types of coping strategies for these stressors were identified: (a) grandparents’ and spousal support, (b) mental strengths, and (c) planning ahead for the future of their family. Practical implications are discussed for supporting CISs. Findings of the current study expand our knowledge about CISs’ challenges and strategies for maintaining work–life balance.